DOI: 10.18174/569974
|View full text |Cite
|
Sign up to set email alerts
|

Method matters : Exploration and reflection on the study of farmers’ demand for vegetatively propagated seed

Abstract: Supporting such new theoretical perspectives on adoption requires methods that are capable of capturing new aspects they include. Currently, a household survey is the most common research method to understand farmers' adoption and demand of (vegetative propagated) planting material (Pircher and Almekinders, 2021; Walker and Alwang, appropriately developed, knowledge is truth, meaning it is certain, accurate and coherent with reality (Park et al., 2020). The other worldview takes the assumption that reality is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 173 publications
0
4
0
Order By: Relevance
“…Introduction of a new variety can be challenging. Research and experience have shown that even though benefits of an improved variety are demonstrated, farmers may still refrain from adoption (Almekinders et al, 2019;Hoogendoorn et al, 2018;Kilwinger et al, 2022). Contextual factors always need to be considered providing insight into a farmer's livelihood and constraints.…”
Section: System Transformationmentioning
confidence: 99%
“…Introduction of a new variety can be challenging. Research and experience have shown that even though benefits of an improved variety are demonstrated, farmers may still refrain from adoption (Almekinders et al, 2019;Hoogendoorn et al, 2018;Kilwinger et al, 2022). Contextual factors always need to be considered providing insight into a farmer's livelihood and constraints.…”
Section: System Transformationmentioning
confidence: 99%
“…Introduction of a new variety can be challenging. Research and experience have shown that even though benefits of an improved variety are demonstrated, farmers may still refrain from adoption Hoogendoorn et al, 2018;Kilwinger et al, 2022). Contextual factors always need to be considered providing insight into a farmer's livelihood and constraints.…”
Section: System Transformationmentioning
confidence: 99%
“…However, as emphasised in Chapter 7, to tailor varieties to the specifics of farmer demand, a solid understanding is required of the wide diversity of farmers and farming systems, in terms of resource endowments and the local agroecological, socioeconomic and cultural conditions in which farmers operate. While, according to formal, agro-industrial sector standards, quality seed is high-yielding, uniform, genetically pure, healthy, and in the proper physiological stage, this may not fully match with the needs and meanings that compose quality in the eyes of smallholder farmers (Kilwinger, 2022). This raises the question how to accommodate, with the development of hybrid potato varieties, the heterogeneity among farmers in Sub-Saharan Africa.…”
Section: Hybrid Potato Variety Development and Selectionmentioning
confidence: 99%
“…However, as emphasised in Chapter 7, to tailor varieties to the specifics of farmer demand, a solid understanding is required of the wide diversity of farmers and farming systems, in terms of resource endowments and the local agroecological, socioeconomic and cultural conditions in which farmers operate. While, according to formal, agro-industrial sector standards, quality seed is high-yielding, uniform, genetically pure, healthy, and in the proper physiological stage, this may not fully match with the needs and meanings that compose quality in the eyes of smallholder farmers(Kilwinger, 2022). This raises the question how to accommodate, with the development of hybrid potato varieties, the heterogeneity among farmers in Sub-Saharan Africa.…”
mentioning
confidence: 99%